2021
DOI: 10.3390/antiox10070995
|View full text |Cite
|
Sign up to set email alerts
|

Potential Activity Mechanisms of Aesculus hippocastanum Bark: Antioxidant Effects in Chemical and Biological In Vitro Models

Abstract: The bark of Aesculus hippocastanum is an herbal remedy used in conditions connected with vascular insufficiency; however, there is a lack of data concerning its mechanisms of action. The present work is a preliminary investigation into some of the potential directions of the bark activity. The phytochemically (qualitative UHPLC-PDA-MS/MS and quantitative UHPLC-PDA assays) characterized extract and its four main constituents (esculin, fraxin, (‒)-epicatechin and procyanidin A2) were first evaluated in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The antioxidant effects seen in the study correlate with those of published work, although some differences have occurred due to the methodology and type of extract that was used in the study [26]. The high density of procyanidins may be an explanation for the higher activity in fruit extracts as this compound is often associated with antioxidant effects [21]. The large standard deviation that was seen not only in the antioxidant results, but the antifungal assay too, could also be explained by the minor difference in chemistry across species.…”
Section: Antioxidant Activitysupporting
confidence: 71%
See 1 more Smart Citation
“…The antioxidant effects seen in the study correlate with those of published work, although some differences have occurred due to the methodology and type of extract that was used in the study [26]. The high density of procyanidins may be an explanation for the higher activity in fruit extracts as this compound is often associated with antioxidant effects [21]. The large standard deviation that was seen not only in the antioxidant results, but the antifungal assay too, could also be explained by the minor difference in chemistry across species.…”
Section: Antioxidant Activitysupporting
confidence: 71%
“…Aside from aescin other chemical constituents within horse chestnuts have bioactivity [14][15][16][17], i.e., the similarly named aesculin, not to be confused with aescin, is a coumarin glycoside that is well known for anticancer and antimicrobial effects [18,19]; fraxins have hepatoprotective properties and the ability to positively affect the immune system [18,20]; procyanidins have long been associated with health benefits as antioxidants, vascular protective compounds [21], and are protective against neurodegenerative diseases [22]; and kaempferol and quercetin derivatives inhibit biofilm formation and alleviate pain and inflammation [23]. Overall, the combination of the bioactive compounds gives horse chestnut extracts numerous beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 18 demonstrated dose-dependent scavenging potential and have particularly advantageous capacity against peroxynitrite (3.37–13.26 mmol AA/g), hydroxyl radical (5.03–8.91 mmol AA/g) and superoxide radical (3.50–5.50 mmol AA/g) (ascorbic acid (AA) was used as positive control.) [ 85 ]. Many flavan-4-ol glycosides also showed remarkable antioxidant and free radical scavenging properties.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Most of the research conducted on A. hippocastanum focused on its properties to regulate circulatory system imbalances and relieve attacks of hemorrhoids [33]. In a study conducted by…”
Section: -2-susceptiility Of Clinical Strains To Antibioticsmentioning
confidence: 99%
“…Owczarek et al [33] on the composition of A. hippocastanum bark, it has been reported that this plant presents mainly two groups of compounds: coumarins and proanthocyanidins. Among the coumarins there was mainly esculin (over 17%) and fraxin (over 7%) while among the proanthocyanidins, the authors found epicatechin (over 6%) and procyanidin A2 (over 5%) (Figure 2) [33]. Owczarek et al [33] finally conclude that, in total, about 40% of the A. hippocastanum bark extract could be attributed to simple phenolics compounds detectable by LC-PDA.…”
Section: -2-susceptiility Of Clinical Strains To Antibioticsmentioning
confidence: 99%